Paisajes mineros en un área marginal del Reyno de Chile: un abordaje desde la antropología-ambiental al Corregimiento de Cuyo (1683-1756) - Sironi, Osvaldo (Anuario de Historia de América Latina, 2025)
This paper analyzes the characteristics of the mining metallurgical activities developed in the Andean peripheral region of Cuyo (Argentina) during the first eighteenth century, according to the periodization proposed by Contreras Carranza. From a perspective that fuses Historical Anthropology and Environmental History, we will analyze the role that this activity played in the socio-historical dynamics of the area, based on the technological strategies deployed in the exploitation and production of minerals, as well as in the identification of the socio-ethnic groups that were affected by the work recorded in the study area. Likewise, this disciplinary fusion will allow us to construct analytical categories to understand the mode of production of the synchronous and/or diachronic socio-environmental impact of the mining sites of the late colonial world of Cuyo.
Keywords: Historical Anthropology; Mining; Cuyo (Argentina); 18th century; Environmental History.